Influence of irradiation by 60Co gamma-quanta on reliability of IR-LEDs based upon AlGaAs heterostructures; Physica Status Solidi (C); Vol. 13, iss. 10-12 - Gradoboev A. V. Aleksandr Vasilyevich (2016, 2016)
Title screen